AGRARIAN REFORM POLICY AS A TOOL FOR RESOLVING LAND TENURE CONFLICTS INVOLVING FORMER BUSINESS USE RIGHTS OF PT GUCI SARI TEGAL - Yuniar Sabdaningtyas; Lego Karjoko; Anti Mayastuti (SOSIOEDUKASI, 2026)
This study aims to formulate agrarian reform policy as an instrument for resolving land tenure conflicts on the former Right to Cultivate (HGU) land of PT Guci Sari in Tegal Regency. This research employs an empirical legal method with a qualitative approach. Research data sources were obtained through primary data in the form of interviews and observations, while secondary data were gathered from other legal sources. The results indicate that Agrarian Reform has served as tangible evidence of an effective conflict resolution instrument through a coordinative mediation mechanism. Based on Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution (ADR Law), the two-phase conflict resolution on the former HGU land of PT Guci Sari was carried out through non-litigation channels emphasizing the principle of deliberation (musyawarah). The first phase involved mediation by the National Land Agency (BPN) to unravel the company's historical claims, whose rights had expired since 2016. The second phase was resolved through mediation by the Agrarian Reform Task Force (GTRA) along with cross-sectoral agencies, including the Forest Management Unit (KPH), the Housing and Settlement Areas Agency (Perkim), and the Pemalang Regency Government, to mediate land disputes between tenant farmers from Tegal and Pemalang Regencies. This implementation aligns with the problem-solving strategy theory to achieve a fair agreement. Ultimately, this policy produced concrete results in the form of determining the subjects and objects of asset redistribution, providing legal certainty through the issuance of Land Ownership Certificates (Sertifikat Hak Milik) for the tenant farmers.